2007
DOI: 10.1553/cia148s21
|View full text |Cite
|
Sign up to set email alerts
|

The moving bump in the light curves of SS For and RR Lyr

Abstract: High-precision multisite photometry was used to investigate the bump occurring before minimum light in the light curves of the two RRab Blazhko stars RR Lyr and SS For. For both stars the phase of the bump was found to be variable with a period equal to the Blazhko period. There seems to be a direct connection between the behavior of the bump and the Blazhko effect. As most models connect the phase of the bump to the stellar radius, a variable bump phase may provide constraints to the models for explaining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Indeed, in Blazhko stars, the additional shock s3', which merges with the front s4+s3, must strongly affect the intensity and phase of the bump, as observed by Guggenberger & Kolenberg (2006. In some cases, the bump may even disappear temporarily.…”
Section: Moving Bumpmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, in Blazhko stars, the additional shock s3', which merges with the front s4+s3, must strongly affect the intensity and phase of the bump, as observed by Guggenberger & Kolenberg (2006. In some cases, the bump may even disappear temporarily.…”
Section: Moving Bumpmentioning
confidence: 87%
“…The variation of the parameters could be studied in many details and with unprecedented precision. First Guggenberger & Kolenberg (2006 showed that in the phase of the bump in the light curve of SS For and RR Lyr (RRab stars) is variable with a period equal to the Blazhko period. They conclude that there is a direct connection of the Blazhko effect and the "motion" of the bump.…”
Section: Variation Of the Pulsation Parameters During The Blazhko Cyclementioning
confidence: 99%
“…These bumps are probably connected with hypersonic shock waves (Chadid et al 2008), and the spreading of the residuals suggests a link between pulsation and atmosphere dynamics. More precisely, this could be the clue to an interaction between the Blazhko phenomenon and the atmosphere's dynamics (Guggenberger & Kolenberg 2006), since monoperiodic RR Lyrae stars also have very regular light curves in the presence of this bump (Poretti 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is well known that the light curve shape of RR Lyrae stars changes during the Blazhko cycle. Also, secondary features like the so-called bump are known to change during the modulation [6] resulting in changing amplitudes of the harmonics which describe the shape of the light curve. As mentioned earlier, 7 harmonics were included into the fit.…”
Section: Influence Of Nonlinearitiesmentioning
confidence: 99%